Research on low-Impact development layouts in old urban residential communities based on multi-objective optimization - Fuqin Liu; Yijun Fan; Xinran Liu; Yanjuan Li (PLoS ONE, 2025)
Challenges such as poor drainage systems and limited space for renovation often arise during the sponge city transformation of old urban residential communities. This research focuses on an old residential community in Beijing utilizing the SWMM in combination with the NSGA-II algorithm. A Pareto optimal curve was identified iteratively, with construction costs, runoff reduction effects, and node overload time as the optimization objectives and the maximum area for the low impact development (LID) layout as a constraint. After transformation using LID measures, the runoff reduction rate is directly proportional to the construction cost. However, the rate of runoff reduction increases marginally when the construction cost exceeds 1.4 million yuan. Additionally, the average node overload time decreases as the construction cost and runoff reduction rate increase. Therefore, selecting a transformation scheme requires comprehensive consideration of factors such as budget and land use type in practice.